Implementation of Learning Organization in Public Health Center: A Systematic Literature Review on Enablers, Barriers, and Organizational Outcomes - Sudirman Sudirman; Subardin AB; Sri Purwiningsih; Imelda Kantohe; Desak Eka Susanawati; Lexy Kareba (Pancasakti Journal Of Public Health Science And Research, 2026)
Public health services face various complex challenges such as limited human and financial resources, fragmentation of health information systems, and policy dynamics and accreditation requirements. These conditions require adaptive organizational capacity and a focus on continuous learning to maintain consistent service quality. This study aims to analyze (1) implementation characteristics, (2) enablers and barriers to implementation, and (3) the impact on organizational performance and service quality. This study is a descriptive literature review using data from Google Scholar with the keyword “learning organization.” The study includes open-access, full-text, English-language articles indexed in Scopus that were filtered using the Rapid Journal Quality Check tool and published between 2021 and 2025 in the field of health. A total of 26 articles meeting these criteria were analyzed using a thematic analysis approach with the SciSpace tool. LO implementation is characterized by continuous learning processes at the individual and team levels, data-based reflection, and knowledge-sharing systems between organizational units. LO implementation is influenced by supporting factors such as transformative leadership, interprofessional collaboration, mentoring systems, and policy support, while obstacles include hierarchical organizational culture, limited resources, and inadequate digital infrastructure. The implementation of LO has proven to strengthen adaptive capacity, improve organizational effectiveness, and support the sustainability of primary health care quality improvement